2012
DOI: 10.1038/ijos.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-ups of revascularized immature necrotic teeth: three case reports

Abstract: Revascularization of immature necrotic teeth is a reliable treatment alternative to conventional apexogenesis or apexification. In case 1, a 12-year-old boy had his necrotic, immature mandibular left second premolar treated with a revascularization technique. At a 24-month follow-up, periapical radiolucency had disappeared and thickening of the root wall was observed. In cases 2 and 3, a 10-year-old boy had his necrotic, immature, bilateral mandibular second premolars treated with the same modality. At 48-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 23 publications
2
35
0
3
Order By: Relevance
“…These results were confirmed by CT scans and there were no significant differences between the experimental and control teeth. Similar results with continued root development have been reported in cases that have been treated successfully with regeneration/revitalization protocols (Jung et al 2008, Torabinejad & Turman 2011, Jeeruphan et al 2012, Kim et al 2012a.…”
Section: Discussionsupporting
confidence: 84%
“…These results were confirmed by CT scans and there were no significant differences between the experimental and control teeth. Similar results with continued root development have been reported in cases that have been treated successfully with regeneration/revitalization protocols (Jung et al 2008, Torabinejad & Turman 2011, Jeeruphan et al 2012, Kim et al 2012a.…”
Section: Discussionsupporting
confidence: 84%
“…From the histological analysis, it was observed that there was ingrowth of connective tissue into the canal space and varied levels of mineralized tissue along the canal walls as well as "islands" of mineralized tissue embedded within the newly formed tissue. Since dental pulp is a type of connective tissue with a rich supply of bs_bs_banner 9 3 Not reported Pulp necrosis (n = 1), previously initiated therapy (n = 1), previous revascularization (n = 1), symptomatic apical periodontitis (n = 1), acute apical abscess (n = 2)…”
Section: A Brief Historical Overviewmentioning
confidence: 99%
“…Reviews at 36 months showed continued root maturogenesis for some cases [30]. Only two studies followed the cases for 48-60 months [29,34], which leaves doubts on the long-term prognosis. There is also difficulty in maintaining patient monitoring for such long periods, as reported by Ding et al [31] and Nagy et al [24].…”
Section: Discussionmentioning
confidence: 93%
“…This was followed by the application of an antibiotic paste, formed by ciprofloxacin, metronidazole and minocycline, as recommended by Banchs and Trope [15]. In order to prevent discoloration of the tooth, three studies replaced Minocycline with Cefaclor [29], Doxycycline [24] and Amoxicillin [30]. The time the drugs spent in the root canal ranged between 1-4 weeks, until no more exudate, swelling, sinus tract and pain or tenderness to percussion were observed.…”
Section: Resultsmentioning
confidence: 99%